IMPROVING CUSTOMER SATISFACTION OF SELF-SERVICE BANKING (CS DIGITAL) CASE STUDY: PT BANK AAA BRANCH X (The Indonesian Journal of Business Administration, 2021)
Innovation is needed in various business sectors, including banking. One of the innovations developed by banks in various countries is based on self-service banking services. Likewise, human resources (customer service-service-based) self also play an important role in customer satisfaction with a company. CS Digital is a-service based self service issued by one of the largest private banks in Indonesia. However, it was found in one branch that the use of CS Digital was not optimal. This study will measure how satisfied customers are with-based banking services, self-service namely CS Digital, compared to customer satisfaction with the quality of human (service customer service) and the author will provide some suggestions for optimizing the use of CS Digital, one of the branches of PT Bank AAA. Service quality is measured using 5 dimensions of service quality, convenience, reliability and security, responsiveness, personalization, and tangible and customer satisfaction indicators. From these attributes, it will be calculated how big the gap is between customer expectations and company performance. The calculation of the gap is assisted by the method Importance Performance Analysis (IPA). In this study, there are several problems related to the operation of CS Digital that need to be resolved. These problems include ease of use of CS Digital, lack of clear directions for new users, slow service, and CS Digital is not the first choice for customers to make transactions. Fishbone is used to analyze the root of the problem and to find out the cause and effect of problems that occur at PT Bank AAA branch X. In addition to the fishbone method, the author also uses theories regarding service quality to find the main problems in PT Bank AAA branch X. The root of the problem from PT Bank AAA branch X, I tried to give suggestions to optimize the use of CS Digital so that it can help reduce queues and increase branch productivity as expected.Keywords: Customer satisfaction, service quality, fishbone